Pengaruh Komunikasi dan gaya Kepemimpinan Terhadap Motivasi Kerja di Kantor Kelurahan Gunung Telihan - Susanti; Ayuditasari (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to find out how communication and leadership style influence work motivation in the Gunung Telihan.pi sub-district office. This research uses an associative quantitative method to determine the relationship between two or more variables. The subjects in this research were employees at the Gunung Telihan Village Office. The results of the research show that Communication and Leadership Style have a positive and significant effect, which means there is a relationship between Communication and Leadership Style on Work Motivation in the Gunung Telihan District Office.